Features of development of the competition in the sphere services of physical culture and sport - N. V. Filonenko; N. A. Ushakova (Путеводитель предпринимателя)
In article the aspects of foreign and domestic scientists concerning competition development are considered, its essence and a concept reveals, the factors constraining and promoting development of the competition in service trade of physical culture and sport (FKIS), types and signs come to light.